Fluorescence Spectrometric Determination of Drugs Containing 𝜶-Methylene Sulfone/Sulfonamide Functional Groups Using N1-Methylnicotinamide Chloride as a Fluorogenic Agent - Khaled M. Elokely; Mohamed A. Eldawy; Mohamed A. Elkersh; Tarek F. El-Moselhy (International Journal of Analytical Chemistry)
A simple spectrofluorometric method has been developed, adapted, and validated for the quantitative estimation of drugs containing 𝛼-methylene sulfone/sulfonamide functional groups using N1-methylnicotinamide chloride (NMNCl) as fluorogenic agent. The proposed method has been applied successfully to the determination of methyl sulfonyl methane (MSM) (1), tinidazole (2), rofecoxib (3), and nimesulide (4) in pure forms, laboratory-prepared mixtures, pharmaceutical dosage forms, spiked human plasma samples, and in volunteer's blood. The method showed linearity over concentration ranging from 1 to 150 𝜇g/mL, 10 to 1000 ng/mL, 1 to 1800 ng/mL, and 30 to 2100 ng/mL for standard solutions of 1, 2, 3, and 4, respectively, and over concentration ranging from 5 to 150 𝜇g/mL, 10 to 1000 ng/mL, 10 to 1700 ng/mL, and 30 to 2350 ng/mL in spiked human plasma samples of 1, 2, 3, and 4, respectively. The method showed good accuracy, specificity, and precision in both laboratory-prepared mixtures and in spiked human plasma samples. The proposed method is simple, does not need sophisticated instruments, and is suitable for quality control application, bioavailability, and bioequivalency studies. Besides, its detection limits are comparable to other sophisticated chromatographic methods.